Protection of HDG Steel Using ORMOSIL Coatings Enhanced with CeO2(5-ATDT)- Ceramic Nanocontainers - Kordas, George (Applied Science and Engineering Progress, 2023)
First, we studied the anticorrosion efficiency of the corrosiveness inhibitors CeO2, 5-amino-1,3,4-thiadiazole- 2-thiol (5-ATDT), Ce(NH4)2(NO3)6 in hot-dip galvanized zinc (HDG) steel. The best protection is shown by the compound Ce(NH4)2(NO3)6 among the three. Second, CeO2 ceramic nanocontainers were prepared, which were loaded with 5-ATDT. Third, organically modified silica (ORMOSIL) coatings were produced on hot-dip galvanized zinc (HDG) steel, which was reinforced with CeO2(5-ATDT) nanocontainers. Finally, the anticorrosion protection of these composites was studied using the Frequency Response Analysis (FRA) method, and it was established to reinforce ORMOSIL with CeO2(5-ATDT); inducing the phenomenon of “self-healing”.